Upaya Meningkatkan Hasil Belajar Matematika Melalui Penerapan Model Pembelajaran Berbasis Masalah - Butar Butar, Toni (JURNAL GLOBAL EDUKASI, 2020)
Abstract: The root of the problem in this study is poor student learning outcomes. Toovercome this problem, this study applies a problem-based learning model. This researchis a classroom action research, with the research subjects of class IX-2 SMP Negeri 3Muara, totaling 32 people. This research's object is student learning outcomes through theapplication of problem-based learning on quadratic function material in class IX-2 ofSMP Negeri 3 Muara. The instrument used was a test. The test consists of a pre-test and apost-test, each of which consists of 5 items. In the first cycle, the number of students whoobtained the